Friends With Benefits: Exploring the Phycosphere of the Marine Diatom Skeletonema marinoi - Johansson, Oskar N.; Pinder, Matthew I. M.; Ohlsson, Fredrik; Egardt, Jenny; Töpel, Mats; Clarke, Adrian K. (Frontiers in Microbiology, 2019)
Marine diatoms are the dominant phytoplankton in the temperate oceans and coastal regions, contributing to global photosynthesis, biogeochemical cycling of key nutrients and minerals and aquatic food chains. Integral to the success of marine diatoms is a diverse array of bacterial species that closely interact within the diffusive boundary layer, or phycosphere, surrounding the diatom partner. Recently, we isolated seven distinct bacterial species from cultures of Skeletonema marinoi, a chain-forming, centric diatom that dominates the coastal regions of the temperate oceans. Genomes of all seven bacteria were sequenced revealing many unusual characteristics such as the existence of numerous plasmids of widely varying sizes. Here we have investigated the characteristics of the bacterial interactions with S. marinoi, demonstrating that several strains (Arenibacter algicola strain SMS7, Marinobacter salaries strain SMR5, Sphingorhabdus flavimaris strain SMR4y, Sulfitobacter pseudonitzschiae strain SMR1, Yoonia vestfoldensis strain SMR4r and Roseovarius mucosus strain SMR3) stimulate growth of the diatom partner. Testing of many different environmental factors including low iron concentration, high and low temperatures, and chemical signals showed variable effects on this growth enhancement by each bacterial species, with the most significant being light quality in which green and blue but not red light enhanced the stimulatory effect on S. marinoi growth by all bacteria. Several of the bacteria also inhibited growth of one or more of the other bacterial strains to different extents when mixed together. This study highlights the complex interactions between diatoms and their associated bacteria within the phycosphere, and that further studies are needed to resolve the underlying mechanisms for these relationships and how they might influence the global success of marine diatoms.